An investigation into the relationship between nutritional status, dietary intake, symptoms and health-related quality of life in children and young people with juvenile idiopathic arthritis: a systematic review and meta-analysis - Najmeh Zare; Maedeh Mansoubi; Shelly Coe; Ali Aminalsharieh Najafi; Kathryn Bailey; Kathryn Harrison; Joanna Sheehan; Helen Dawes; Karen Barker (BMC Pediatrics, 2023)
Abstract Background The association between diet, symptoms and health related quality of life in children and young people with Juvenile idiopathic arthritis (JIA) is not clearly understood. The objectives of this systematic review and meta-analysis were to explore the evidence for a relationship between nutritional status, dietary intake, arthritis symptoms, disease activity and health-related quality of life in children and young people with JIA considering both observational and interventional studies separately. Method The databases PubMed, CINAHL, PsycINFO, Web of Science and Cochrane were searched in October 2019, updated in September 2020 and October 2021. Searches were restricted to English language, human and age (2–18 years old). Studies were included if they measured the effect of dietary supplements, vitamins or minerals, or diet in general, on quality of life and/ or arthritis symptom management. Two researchers independently screened titles and abstracts. Full texts were sourced for relevant articles. PRISMA guidelines were used for extracting data. For variables (vitamin D and disease activity), a random-effects meta-analysis model was performed. Two authors using a standardized data extraction form, extracted data independently. Results 11,793 papers were identified through database searching, 26 studies met our inclusion criteria with 1621 participants. Overall studies quality were fair to good. Results from controlled trial and case control studies with total 146 JIA patients, found that Ɯ-3 PUFA improved the mean active joint count (p < 0.001), Juvenile Arthritis Disease Activity Score (JADAS-27) (p < 0.001) and immune system (≤ 0.05). Furthermore, n-3 and n-6 PUFAs have a negative correlation with CRP (C-reactive protein) and ESR (erythrocyte sedimentation rate) (p < 0.05). Improvement in JIA symptoms were observed in one case, one pilot and one exploratory study with overall 9 JIA patients after receiving Exclusive Enteral Nutrition (EEN) which contains protein and what is required for a complete nutrition, A clinical trial study found Kre-Celazine nutrition (composed of a proprietary alkali buffered, creatine monohydrate and fatty acids mixture) in 16 JIA patients improved symptoms of JIA. No association was found between vitamin D and disease activity from three studies. Height and weight values in relation to healthy controls varied across studies (p = 0.029). Conclusions We were only able to include small studies, of lower design hierarchy, mainly pilot studies. We found some evidence of lower height and weight across studies in JIA, but were unable to confirm an association between diet, symptoms and health-related quality of life in children and young people with JIA. Well-designed, carefully measured and controlled interventional studies of dietary patterns in combination with important contributing factors such as medication and lifestyle behaviours, including physical activity, are required to determine the impact of diet in improving symptoms and growth patterns in children and young people with JIA, with an aim to improve the quality of their life. Trial registration PROSPERO [CRD42019145587].